Transforming Agriculture in South Sudan : From Humanitarian Aid to a Development Oriented Growth Path - Eliste, Paavo; Forget, Vanina; Veillerette, Benoist; Rothe, Ann-Kristin; Camara, Youssouf; Cherrou, Yamina; Ugo, Edward; Deng, Samuel (Rome, Italy; Washington D.C., United States of America : FAO; World Bank, 2022)
FAO teamed up with the World Bank on this strategic analysis of the investment, policy and institutional support needed to shift South Sudan’s agriculture sector from humanitarian relief to a development-oriented growth path. The team carried out a thorough review of lessons learned in South Sudan and other conflict-affected countries and held consultations with a wide range of stakeholders in the country. As a result, four complementary investment strategies were identified: agriculture production and food security; community resilience and social capital; value chain development and jobs; and peace consolidation. The authors advocate for combining these four strategies in a flexible way, depending on how the shocks currently affecting agriculture (conflict, violence, macro-economic instability, governance, natural disasters) evolve in the coming years. The Government of South Sudan and the World Bank consider this analytical work a milestone that will pave the way for future investments in agriculture and rural development in the country. This publication is part of the Country Investment Highlights series under the FAO Investment Centre’s Knowledge for Investment (K4I) programme.